IMPLEMENTASI MODEL EBIT – EPS DALAM PENGAMBILAN KEPUTUSAN STRUKTUR MODAL PADA PT LIPPO KARAWACI, Tbk. - Ahmad Safiudin (Universitas muhammadiyah malang, 2016)
This research aims to determine the use of an optimal capital structure to meet the needs of additional funds in PT Lippo Karawaci Tbk in 2016. EBIT - EPS analysis was employed to use the model as a tool. The result indicated that a 100% PT. Lippo Karawaci Tbk.’s additional fund is based on debt. As an alternative funding, debt is resulted the highest EPS than others. The debt used can lead interest expense increase. The company needs to pay attention to the risks to avoid bankruptcy.